Elite high jumpers exhibit inadequate nutrient intakes - Bogdanis, G.C.; Veligekas, P.; Selima, E.; Christofi, E.; Pafili, Z. (Journal of Physical Education and Sport, 2013)
High jumpers strive to maintain low body mass and may be at increased risk for inadequate nutrient intakes. Since there is no data on the nutritional status in this sport, this study aimed to evaluate the nutritional intake of elite high jumpers (7 males, 7 females). Athletes were in energy balance (energy intake was equal to energy expenditure and body mass was stable), but their energy intake was among the lowest reported for athletes (148±23 and 142±18 kJ/kg/day, for males and females). Carbohydrate intake of both males and females (3.6±0.8 g/kg/day) was low compared with recommended values, and diet was deficient in several micronutrients such as vitamin D (12% of dietary reference intake, DRI), vitamin E (34% DRI), folate (46% DRI), calcium (78% DRI) and iron (55% DRI, for females only). These low carbohydrate and micronutrient intakes may negatively affect training quality and adaptations and may jeopardize the athletes' health. © JPES.
Keywords: Carbohydrate intake; Nutrition; Track and field